THEORETICAL FEASIBILITY OF INTERACTIVE MULTIMEDIA BASED ON ARTICULATE STORYLINE IN LIQUID PRESSURE - NUR INDASARI, PRILY; BUDIYANTO, MOHAMMAD (PENSA E-JURNAL: PENDIDIKAN SAINS, 2019)
Abstract This study aims to produce interactive multimedia based on Articulate Storyline in liquid pressure for 8th grade which is theoretically feasible based on media validity. The research method used is R & D (Research and Development) which is limited to stage 5, product revision. The results of the study show that the interactive multimedia validity gets very decent criteria. In the aspect of media format, the percentage is 92.86%, while the material aspect of the media has a percentage of 94.44%. The results of the study indicate that interactive multimedia based on Articulate Storyline is theoretically feasible. Keywords: interactive multimedia, Articulate Storyline, liquid pressure